Electron transport mechanism in rf‐sputtered amorphous zinc oxynitride thin films. Issue 7 (27th May 2016) - Reinhardt, Anna; Frenzel, Heiko; von Wenckstern, Holger; Spemann, Daniel; Grundmann, Marius
Abstract: Abstractauthoren We discuss the carrier transport mechanism in amorphous zinc oxynitride (ZnON) thin films fabricated by means of long‐throw magnetron sputtering. ZnON films were radio‐frequency sputtered from a metallic zinc target in a reactive atmosphere consisting of N 2, O 2, and Ar. The electrical conductivity of the films was controlled via variation of the deposition pressure and substrate temperature. Room temperature deposition yields amorphous, n‐type semiconducting ZnON thin films with a maximum Hall mobility of 25 cm 2 V − 1 s − 1 and carrier concentrations of ∼ 10 18 cm − 3 . The mobility can be further increased up to the 40 cm 2 V − 1 s − 1 range by moderate substrate heating or annealing up to 200 ∘ C while maintaining the amorphous phase. From temperature‐dependent Hall effect measurements, we deduced that a percolation conduction model is most likely for the electron transport in the as‐grown ZnON thin films. For annealed samples, a quasi‐metallic behavior is observed.